Characterization of rabbit corneal damage produced by Serratia keratitis and by a serratia protease. - Lyerly, D (1981)
The structural alterations elicited in the rabbit corneal stroma by experimental Serratia marcescens keratitis and by a highly purified serratia protease preparation were compared by gross observation, biochemical analyses, and electron microscopic examination of the affected tissue. Acute inflammation, liquefactive necrosis of the cornea, and descemetocele formation occurred during the development of the infection and after the intracorneal injection of submicrogram amounts of the protease. In vitro incubation of insoluble corneal stromal tissue with the bacterium or with the protease resulted in solubilization of the stromal proteoglycan ground substance; however, specific collagenase activity was not detected. Electron microscopic examination of corneas damaged by the bacterial infection and by the protease revealed loss of ruthenium red staining of the proteoglycan ground substance and dispersal of ultrastructurally normal collagen fibrils. Thus, our findings indicate that the major corneal damage which occurs during serratia keratitis and after the injection of the serratia protease is caused by solubilization and loss of the ground substance of the tissue. In addition, the observation that the major structural alterations observed during serratia keratitis can be reproduced by the bacterial protease supports the idea that the enzyme is involved, at least in part, with the production of severe corneal damage by the bacterium.